High-Throughput Screening for Linear Ubiquitin Chain Assembly Complex (LUBAC) Selective Inhibitors Using Homogenous Time-Resolved Fluorescence (HTRF)-Based Assay System. (December 2018) - Katsuya, Ken; Hori, Yuji; Oikawa, Daisuke; Yamamoto, Tomohisa; Umetani, Kayo; Urashima, Toshiki; Kinoshita, Tomomi; Ayukawa, Kumiko; Tokunaga, Fuminori; Tamaru, Masahiro
The nuclear factor κB (NF-κB) pathway is critical for regulating immune and inflammatory responses, and uncontrolled NF-κB activation is closely associated with various inflammatory diseases and malignant tumors. The Met1-linked linear ubiquitin chain, which is generated by linear ubiquitin chain assembly complex (LUBAC), is important for regulating NF-κB activation. This process occurs through the linear ubiquitination of NF-κB essential modulator, a regulatory subunit of the canonical inhibitor of the NF-κB kinase complex. In this study, we have established a robust and efficient high-throughput screening (HTS) platform to explore LUBAC inhibitors, which may be used as tool compounds to elucidate the pathophysiological role of LUBAC. The HTS platform consisted of both cell-free and cell-based assays: (1) cell-free LUBAC-mediated linear ubiquitination assay using homogenous time-resolved fluorescence technology and (2) cell-based LUBAC assay using the NF-κB luciferase reporter gene assay. By using the HTS platform, we performed a high-throughput chemical library screen and identified several hit compounds with selectivity against a counterassay. Liquid chromatography–mass spectrometry analysis revealed that these compounds contain a chemically reactive lactone structure, which is transformed to give reactive α, β-unsaturated carbonyl compounds. Further investigation revealed that the reactive group of these compounds is essential for the inhibition of LUBAC activity.